ANALISIS PENERAPAN HYGIENE SANITASI KANTIN KARYAWAN HOTEL DAIMA PADANG - Farandy, Rahadian Ray (RC-INSTITUT, 2019)
This study aims to see how the level of hygiene of canteen employees at Daima Hotel Padang. This research consists of four indicators, namely: clean water, sewerage, trash cans and washing places. This type of research is descriptive research with qualitative data.The population in this study were employees of the Daima Padang Hotel. Data is collected by interview, observation and documentation.The results of this study are: 1) Clean water used at the Daima Padang Hotel has met sanitation standards and passed the LAIK Hygiene sanitation test from the Ministry of Health,2) Sewerage in Daima Hotel does not meet sanitary requirements because the sewerage at Daima Hotel is cleaned only once every two weeks,3) The trash can at Daima Hotel does not meet sanitary requirements because the trash can is near food that has been processed and also the trash can does not use trash cover, and the waste is not separated according to its type,and 4) The equipment washing place should have three tubs that are in accordance with the requirements set by the Ministry of Health, while at Hotel Daima only have two wash basin.